Songs Before Sirens: Ornithotherapy as A Tool for Stress Reduction and Academic Support - Katerynych, Petro (Studia Ecologiae et Bioethicae, 2026)
Background. Attention Restoration Theory posits that natural environments restore depleted cognitive resources, while recent evidence confirms that birdwatching yields mental health, cognitive, and social benefits. Aim. This hypothesis-generating pilot study examined whether a curriculum-embedded birdwatching program is associated with changes in self-reported stress, academic focus, creative blocks, and social connection among students studying under wartime conditions in Kyiv, Ukraine. Methods. Twenty-three audiovisual arts undergraduates (mean age = 20.4 years; 14 women, 9 men; no prior birdwatching experience) completed approximately 10 hours of guided birdwatching across five sessions. A single-group retrospective pretest–posttest survey assessed four constructs using 10-point scales. Open-ended responses captured qualitative mechanisms. Results. Significant pre–post changes were observed: Perceived Stress decreased (d = 3.71), Academic Focus increased (d = 2.46), Creative Blocks decreased (d = 2.93), and Social Connection increased (d = 2.33). These large effect sizes should be interpreted as upper-bound estimates given potential demand characteristics inherent to the retrospective design. Qualitative analysis identified attentional anchoring, affective regulation, and social co-regulation as key mechanisms. Conclusions. A compact birdwatching curriculum integrated into an arts program at a crisis-affected university appears feasible and educationally valuable. The observed associations warrant further investigation using controlled designs to establish causal efficacy.